FACTORS ASSOCIATED TO SMOKING BEHAVIOR IN WORSHIP PLACES IN DENPASAR BALI INDONESIA (Proceedings of the International Conference on Public Health, 2021)
Since 2013, City of Denpasar government has adopted smoke-free law regarding smokefree areas including worship places. However, compliance with smoke-free law at worship placesremains low. The implementation of the law faces several obstacles particularly at Hindu temples sinceit is mostly semi-opened spaces and high social acceptability of smoking where cigarette and smokinghave been deeply engrained within social and religious life. Hence, this study aims to assess factorsthat associated with smoking behavior at worship places particularly at Hindu temple in Denpasar BaliIndonesia. This study was a cross-sectional study, conducted in the city of Denpasar, involving 192samples which selected using multistage random sampling. The data was collected using a structuredquestionnaire then analyzed using path analysis. There were 12 factors analyzed such as past behaviorof smoking, exposure to anti-smoking policies, nicotine dependence, knowledge and attitude regardingsecond-hand smoke, knowledge and attitude regarding implementation of smoke-free law,sociodemographic (age, education), social norms of smoking (descriptive and injunctive). Of the 11factors, 5 factors had a significant effect on smoking behavior. Past behavior of smoking had a directnegative effect with a standardized coefficient (beta) -0.34 (p
Keywords: Smoking behavior, worship places, compliance, smoke-free law, Denpasar Bali